Severe anemia in hospitalized HIV positive adults in the Jackson Memorial Hospital of Miami City - Castro Danós, José (2007)
Introduction: anemia is a common and serious complication of both HIV infection and its treatment. Severe anemia is a life-threatening condition and its causes in these patients are multiple but their frequency is unknown. Objective: of the study was to evaluate the causes of severe anemia in HIV infected adults at the time of admission to Jackson Memorial Hospital (JMH) in Miami. Materials and Methods: we reviewed the cases of severe anemia (hematocrit < 20% on admission) in HIV seropositive adults admitted to JMH between 5/96 to 5/97. Results: there were 53 patients, (27 men, 26 women). The mean CD4 cell count was 47cells/mm3 and 67% of the patients had a CD4 cell count less than 50 cells/mm3. Sixty-four percent of the patients were on antiretroviral therapy, including AZT (94%) and protease inhibitors (29%). The mean hematocrit on admission was 16% and the mean number of units of blood transfused was 4. The most common cause of severe anemia in patients with a CD4 < 50 cells/mm3 was opportunistic infections and with CD > 50 cells/mm3 was medication toxicity. Conclusion: causes of severe anemia in HIV positive patients are multiple and varies with the level of CD4. With a lower CD4 anemia of chronic disease becomes less frequent and opportunistic infections are more common.